Complementary and synergistic effects on osteogenic and angiogenic properties of copper-incorporated silicocarnotite bioceramic: In vitro and in vivo studies. (January 2021) - Wu, Qiang; Xu, Shunxiang; Wang, Xin; Jia, Bo; Han, Yu; Zhuang, Yifu; Sun, Ye; Sun, Zhenyu; Guo, Yaping; Kou, Huamin; Ning, Congqin; Dai, Kerong
Abstract: Promoting bone regeneration to treat bone defects is a challenging problem in orthopedics, and developing novel biomaterials with both osteogenic and angiogenic activities is sought as a feasible solution. Here, copper-silicocarnotite [Cu–Ca5 (PO4 )2 SiO4, Cu-CPS] was designed and fabricated. In this study, the Cu-CPS ceramics demonstrated better mechanical, osteogenic, and angiogenic properties in vitro and in vivo than pure CPS one. Particularly, CPS with 1.0 wt% CuO (1.0Cu-CPS) exhibited the best performance. Additionally, hydroxyapatite with 1.0 wt% CuO (1.0Cu-HA) was used to explore the respective effects of copper and silicon (Si). According to the in vitro results, it indicated that Cu enhanced the osteogenic activity of CPS ceramics although Si played a dominate role in the osteogenic process. Moreover, Cu could promote an early stage of angiogenesis, and the complementary effect of Si and Cu was found in the late phase. Furthermore, the in vivo results illustrated that the synergistic effect of Cu and Si improved bone and vessel regeneration during the degradation of Cu-CPS scaffolds (P < 0.05). Therefore, Cu-CPS ceramics could improve osteogenesis and angiogenesis through the simultaneous effects of Cu and Si, thus, offering a promising treatment option in orthopedic application for bone tissue regeneration. Graphical abstract: Image 1